Determination of macroscopic and microscopic residual stresses in friction stir welded metal matrix composites via neutron diffraction. (1st April 2015) - Zhang, X.X.; Ni, D.R.; Xiao, B.L.; Andrä, H.; Gan, W.M.; Hofmann, M.; Ma, Z.Y.
Abstract: This study presents a new method to determine both the macroscopic and microscopic (including elastic mismatch, thermal misfit and plastic misfit) residual stresses in metal matrix composite (MMC) welds via neutron diffraction. As an illustration, friction stir welded 17 vol.% SiCp/2009Al-T4 plates were investigated. It is shown that the calculation of the thermal misfit plus plastic misfit residual stresses in the metal matrix of the MMC welds is much more accurate by using the absolute unstrained lattice parameter of the SiC powder sample based on the stress equilibrium condition compared with using that of the unreinforced alloy sample. The profiles of the longitudinal ( L ), transverse ( T ) and normal ( N ) components of the total residual stress in the reinforcement are entirely different from those in the matrix. It was found that the profiles and total variations of the L, T and N components of the total residual stress are dominated by those of the macroscopic residual stress in the matrix, and by those of the elastic mismatch residual stress in the reinforcement, revealing a significant load transfer from the matrix to the reinforcement. The maximum total residual stress in the metal matrix of the FSW 17 vol.% SiCp/2009Al-T4 weld could reach up to ∼69% of the yield strength of the 2009Al-T4 alloy. Increasing the rotation rate has small effects on the basic profiles of the total residual stress, apart from increasing the width of the profiles.